An Analysis of Question Papers of Different Boards of Examinations in Social Sciences - Sreekanth, Y. (INDIAN EDUCATIONAL REVIEW, 2007)
The Boards of Education/Examination in India play a significant role in the students’ evaluation and through this the system of education. They follow an elaborate process in question paper setting and marking answer scripts. In the present paper a qualitative analysis of the question papers in social sciences is made across the four boards at secondary level public examination, so as to verify the quality of question paper of these boards. The question paper studied from the point of view of content, framing of questions, types and quality of questions indicate that there is need for constant reviewing of the question paper setting activity.